Therapeutic effect of natural melanin from edible fungus Auricularia auricula on alcohol-induced liver damage in vitro and in vivo - Ruolin Hou; Xin Liu; Xiaoping Wu; Mingfeng Zheng; Junsheng Fu (Food Science and Human Wellness)
This study explored the therapeutic effects of Auricularia auricula melanin (AAM) on alcoholic liver damage in vitro and in vivo. Human normal liver L02 cells were pre-treated with ethanol and then treated with AAM to explore the therapeutic effect of AAM on ethanol-induced hepatocyte injury. The results show that AAM significantly elevated the cell viability, ameliorated the cell morphology, reduced the ROS and increased the GSH/GSSG of ethanol-pretreated L02 cells. Then, mice were administered with ethanol to induce acute alcoholic liver damage, and administered with AAM to further study the therapeutic effect of AAM on alcoholic liver damage in mice. As a result, AAM reduced the levels of ALT, AST, TG, and MDA, increased the levels of ADH, SOD, and CAT in liver damage mice. The therapeutic effect of AAM may be related to inhibition of CYP2E1 expression and activation of Nrf2 and its downstream antioxidase. The research enriched the bioactivity of AAM and provided some ideas for the development of melanin-related health foods.